Assessment of hematological and metabolic marker in relation to NAFLD severity: A gender-based study at Al- Wahda hospital-Derna - Arwa Moftah Bofares; Zeinab Moftah Bofares; Fatma Mohammed Agela; Malak Ahmed Farag; Nahla Salem Rajab; Retaj Khalifa Basher; Saja Salama Moftah; Sara Omar Hussain; Zainab Fathi Farag (Libyan Journal of Medical and Applied Sciences, 2025)
This study aimed to compare various biochemical and hematological parameters between non-alcoholic fatty liver disease (NAFLD) positive and negative individuals, stratified by gender. A significant increase in liver enzymes (AST, ALT), LDL, triglycerides (TG), and ferritin levels was observed in both male and female NAFLD-positive subjects compared to their negative counterparts (p<0.05). conversely, HDL levels were significantly lower in the NAFLD-positive group. Hematological parameters such as hemoglobin (Hb) and mean corpuscular hemoglobin (MCH) showed slight but non-significant variations between groups. White blood cell (WBC) counts were elevated in NAFLD-positive males. Additionally, BMI and HbA1c percentages were significantly higher in NAFLD-positive individuals, suggesting a correlation between metabolic syndrome and fatty liver disease. These findings highlight key biomarkers associated with NAFLD and emphasize the importance of early screening and lifestyle interventions. In conclusion, the study demonstrates that individuals with non-alcoholic fatty liver disease, particularly males, exhibit significant alterations in liver enzymes, lipid profile and metabolic indicators such as BMI and HbA1c. these findings highlight the importance of early detection using non-invasive tools like CT imaging and routine blood test and emphasize the need for gender-specific approaches in the management and prevention of non-alcoholic fatty liver disease.